Vascular-targeted photothermal therapy of an orthotopic murine glioma model. (August 2012) - Day, Emily S; Zhang, Linna; Thompson, Patrick A; Zawaski, Janice A; Kaffes, Caterina C; Gaber, M Waleed; Blaney, Susan M; West, Jennifer L
Aim: To develop nanoshells for vascular-targeted photothermal therapy of glioma.Materials & methods: The ability of nanoshells conjugated to VEGF and/or poly(ethylene glycol) (PEG) to thermally ablate VEGF receptor-2-positive endothelial cells upon near-infrared laser irradiation was evaluated in vitro . Subsequent in vivo studies evaluated therapy in mice bearing intracerebral glioma tumors by exposing tumors to near-infrared light after systemically delivering saline, PEG-coated nanoshells, or VEGF-coated nanoshells. The treatment effect was monitored with intravital microscopy and histology.Results: VEGF-coated but not PEG-coated nanoshells bound VEGF receptor-2-positive cells in vitro to enable targeted photothermal ablation. In vivo, VEGF targeting doubled the proportion of nanoshells bound to tumor vessels and vasculature was disrupted following laser exposure. Vessels were not disrupted in mice that received saline. The normal brain was unharmed in all treatment and control mice.Conclusion: Nanoshell therapy can induce vascular disruption in glioma. Original submitted 27 September 2011; Revised submitted 12 December 2011; Published online 14 May 2012